1997
DOI: 10.1046/j.1365-3040.1997.d01-55.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic responses to temperature of phosphoenolpyruvate carboxykinase type C4 species differing in cold sensitivity

Abstract: Photosynthetic rates, the activities of key enzymes associated with the C4 cycle and ribulose-l,5-bisphosphate carhoxylase (RuBPCase), and the levels of metabolites involved in the C4 cycle were compared between the two phosphoenolpyruvate carboxykinase (PCK) type C4 species Spartina anglica, which is cold-tolerant, and Zoysia japonica, which is cold-sensitive, during exposure to low temperature. Plants of both species grown outside in summer were placed in a growth chamber at 27/20 °C day/night temperatures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 24 publications
(38 reference statements)
1
17
0
Order By: Relevance
“…In chilling-sensitive C 4 species, it has long been proposed that one of the enzymes in the C 4 cycle, notably, PPDK, PEPCase, or NADPmalate dehydrogenase, dissociates at chilling temperature and reduces A (Sugiyama & Boku 1976;Long 1983). Chilling-tolerant C 4 plants have stable forms of PPDK and PEPCase in vivo and thus do not appear to be prone to limitations by these enzymes (Burnell 1990;Simon & Hatch 1994;Matsuba et al 1997). Sugarcane is noted to be one of the more chilling sensitive of crop species, and because of its long growing season, it commonly experiences chilling in higher latitude or elevation within its cultivated range (Grantz 1989).…”
Section: Chilling Effects On Amentioning
confidence: 99%
“…In chilling-sensitive C 4 species, it has long been proposed that one of the enzymes in the C 4 cycle, notably, PPDK, PEPCase, or NADPmalate dehydrogenase, dissociates at chilling temperature and reduces A (Sugiyama & Boku 1976;Long 1983). Chilling-tolerant C 4 plants have stable forms of PPDK and PEPCase in vivo and thus do not appear to be prone to limitations by these enzymes (Burnell 1990;Simon & Hatch 1994;Matsuba et al 1997). Sugarcane is noted to be one of the more chilling sensitive of crop species, and because of its long growing season, it commonly experiences chilling in higher latitude or elevation within its cultivated range (Grantz 1989).…”
Section: Chilling Effects On Amentioning
confidence: 99%
“…Furthermore, an analysis of transgenic F. bidentis with antisense PPDK gene constructs showed that PPDK shares control of C 4 photosynthetic rate with Rubisco under ambient CO 2 and high light (Furbank et al, 1997). A key role for PPDK in low temperature tolerance is also inferred in two chilling-tolerant PEP carboxykinase type C 4 species, which apparently maintain photosynthetic rates at low temperature by bypassing PPDK in PEP synthesis, via PEP carboxykinase (Smith and Woolhouse, 1983;Matsuba et al, 1997). Although analysis of the cDNA sequences for PPDK in M. 3 giganteus and maize have failed to reveal any differences in putative amino acids sequences that could confer cold tolerance, the amount of PPDK was reported to increase significantly in M. 3 giganteus when grown at low temperature.…”
mentioning
confidence: 98%
“…Pyruvate orthophosphate dikinase (PPDK, EC 2.7.9.1) and phosphoenolpyruvate (PEP) carboxylase (PEPCase, EC 4.1.1.31) can both dissociate below 8°C to 12°C in vitro (Sugiyama and Boku, 1976;Edwards et al, 1985;Krall and Edwards, 1993). However, considerable species and ecotypic variability has been noted, and these steps are not fundamentally prone to failure at low temperatures in vivo (Leegood and Edwards, 1996;Matsuba et al, 1997).The possibility that the bundle sheath reactions may limit C 4 photosynthesis at suboptimal temperatures has received less attention. Bjö rkman and Pearcy (1971) found that the activation energy (Ea) of photosynthesis was similar to that of Rubisco (EC 4.1.1.39) in several warm-climate C 3 and C 4 species.…”
mentioning
confidence: 99%